Descriptions of two new Vietomartyria species (Lepidoptera, Micropterigidae) from China - Liao, Cheng-Qing; Hirowatari, Toshiya; Huang, Guo-Hua (European Journal of Taxonomy, 2020)
Micropterigidae is a family of Lepidoptera characterized by plesiomorphic morphological characters. Presently, this family consists of more than 22 genera and is distributed throughout all biogeographic realms. Vietomartyria Hashimoto & Mey, 2000 presently consists of six species mainly from South China. Two new species of the genus, V. wuyunjiena sp. nov. and V. maoershana sp. nov., are described herein from China; adult genitalia and wing venation are illustrated. Some biological accounts of the new species are also provided. A key to all described Vietomartyria species is given.